Men's Perspectives on Their Grooming Practices and Appearance Concerns: A Mixed Methods Study. Issue 2 (June 2022) - Hamshaw, Richard J. T.; Gavin, Jeff
This mixed method study explores importance of and influences on men's grooming behaviors and appearance concerns. Survey data from 83 men based in the United Kingdom showed high social media users engaged in significantly more grooming behaviors than low users. Gay men viewed grooming as significantly more important and implemented more grooming habits than straight men. Qualitative responses yielded themes relating to standards set by traditional media and the blurring of boundaries between traditional and new forms of (social) media. Themes reflected the freedom and constraints of sexuality in relation to grooming as well as the management of attraction and status. More research is needed to consider the impact grooming pressures and influences might have on men in the future.